Matrix server implementation - Belčenko, Alexandr (2024)
This work is primarily concerned with the open-source standard Matrix, developed in 2014 and popularised in the late 2010s, headed mainly by The Matrix.org Foundation as well as their for-profit cousin Element. The goal is to set up and configure a working instance of Synapse, one of the most popular servers built on the standard. Initially, the Matrix protocol is introduced with a basic description of its history and fundamental concepts needed to understand its function. Then, there is a general overview of the current state of development of several matrix servers and clients, as well as some uses of the protocol notable for either their scale or the organisation behind them. Next comes the summary of the historical and current competition associated with the field. Finally, there is a detailed description of the Synapse implementation itself, meant for a reader to potentially be able to follow it as an example for their own projects. This also includes basic statistics about the server's performance, requirements, and possible future improvements.